Morbidity Pattern among Out-Patients Attending Urban Health Training Centre in Srinagar - Santosh Kumar; Haroon Ali; Amit Kumar Singh; Abhishek Raj (Intelektual Pustaka Media Utama, 2018)
The current study was designed to identify the morbidity pattern of out-patients attending Urban Health Training Centre in an urban area of a medical college in Srinagar, Pauri Garhwal district, Uttarakhand, North India. The present study record-based retrospective study was conducted among the out-patients attending the regular clinic at the Urban Health Training Centre, of a medical college in Srinagar city of Uttarakhand State of North India during the study period of one year in 2014. Data was retrieved from the OPD registers maintained at the clinic. Data was collected pertaining to socio-demographic profile, morbidity details and treatment pattern. Diseases were identified using the International Classification of Diseases (ICD-10) code. Descriptive analysis was done. During the study period, a total of 9343 subjects attended the OPD. Among them, majority of them (60%) were females. More than half (56 %) belonged to the age group of 35-65 year age-group. The association of disease classification was found to be statistically significant with respect to gender. The leading morbidity of communicable disease was found to be certain infectious and parasitic diseases especially Typhoid whereas musculoskeletal system and connective tissue disorders were the most common cause among morbidity due to NCDs. Out of all, typhoid was found to cause maximum of morbidity among the subjects. The present study highlights the morbidity pattern of communicable and NCDs among the population of hilly areas of Garhwal, Uttarakhand India. Priority should be preferred for the regular tracking of diseases in terms of preventive and promotive aspects. Morbidity in the out- door clinics reflects the emerging trend of mixed disease spectrum burden comprising communicable and non-communicable diseases.